Melanotic Oncocytic Metaplasia of the Nasopharynx: An Unusual Case Report - Barbara Verro (Iranian Journal of Otorhinolaryngology, 2021)
Introduction: Melanotic oncocytic metaplasia of the nasopharynx is an uncommon disease, usually asymptomatic, that could be misdiagnosed for melanoma, because of its macroscopic features. For this reason, is necessary to know it thoroughly and to take it into account in the differential diagnosis.   Case Report: A 69-year-old Italian woman presented to our Otorhinolaryngology Clinic with a 1-month history of sore throat. She has been a smoker for several years. During the nasopharyngoscopic examination, grey-brown, irregular and slightly elevated lesions, measuring few millimetres, were found near the right Eustachian tube opening. The preliminary diagnostic hypothesis was malignant disease. After biopsy and histopathological assessment, the lesion was diagnosed as melanotic oncocytic metaplasia of the nasopharynx that is a benign and rare disease. So, given the multiple lesions and their benign nature, they were controlled with regular nasoscopic examinations.   Conclusion: Melanotic oncocytic metaplasia is a benign lesion of the nasopharynx and it is necessary to emphasize the importance of its clinical awareness for differential diagnosis with malignant lesions.